Writing skills in practice : a practical guide for health professionals - Williams, Diana, 1957- (Arts Therapies., 2002)
This book presents an overview of the development of writing skills for both students and practitioners in health care, offering information on all the main areas of writing practice in one volume. Clearly laid out with summary points, practical activities and checklists, it makes relevant information accessible for the busy health professional.